Importance of Pain Acceptance in Relation to Headache Disability and Pain Interference in Women With Migraine and Overweight/Obesity. Issue 5 (13th March 2017) - Lillis, Jason; Graham Thomas, J.; Seng, Elizabeth K.; Lipton, Richard B.; Pavlović, Jelena M.; Rathier, Lucille; Roth, Julie; O'Leary, Kevin C.; Bond, Dale S.
Abstract : Background: Pain acceptance involves willingness to experience pain and engaging in valued activities while pain is present. Though pain acceptance could limit both headache‐related disability and pain interference in individuals with migraine, few studies have addressed this issue. This study evaluated whether higher levels of total pain acceptance and its two subcomponents, pain willingness and activity engagement, were associated with lower levels of headache‐related impairment in women who had both migraine and overweight/obesity. Methods: In this cross‐sectional study, participants seeking weight loss and headache relief in the Women's Health and Migraine trial completed baseline measures of pain acceptance (Chronic Pain Acceptance Questionnaire [CPAQ]), headache‐related disability (Headache Impact Test‐6), and pain interference (Brief Pain Inventory). Migraine headache frequency and pain intensity were assessed daily via smartphone diary. Using CPAQ total and subcomponent (pain willingness and activity engagement) scores, headache frequency, pain intensity, and body mass index (BMI) as predictors in linear regression, headache‐related disability, and pain interference were modeled as outcomes. Results: On average, participants (n = 126; age = 38.5 ± 8.2 years; BMI = 35.3 ± 6.6 kg/m 2 ) reported 8.4 ± 4.7 migraine days/month and pain intensity of 6.0 ± 1.5 on a 0‐10 scale on headache days. After correcting for multiple comparisons (adjusted α  = .008), pain willingness was independently associated with both lower headache‐related disability ( P  < .001; β  = −0.233) and pain interference ( P  < .001; β  = −0.261). Activity engagement was not associated with headache‐related disability ( P  = .128; β  = −0.138) and pain interference ( P  = .042; β  = −0.154). CPAQ total score was not associated with headache‐related disability ( P  = .439; β  = 0.066) and pain interference ( P  = .305; β  = 0.074). Pain intensity was significantly associated with outcomes in all analyses ( Ps  < .001; βs 0.343‐0.615). Conclusions: Higher pain willingness, independent of degree of both migraine severity and overweight, is associated with lower headache‐related disability and general pain interference in treatment‐seeking women with migraine and overweight/obesity. Future studies are needed to clarify direction of causality and test whether strategies designed to help women increase pain willingness, or relinquish ineffective efforts to control pain, can improve functional outcomes in women who have migraine and overweight/obesity.